Lessons from a secular state: extracting the essence of the constitution and its implication on judicial interpretation of human rights provisions in Turkey and Malaysia - Shuaib, Farid Sufian; Tumay, Murat (IIUM Press, International Islamic University Malaysia, 2019)
Malaysia and Turkey, in a different degree and areas, continue to construct Islamic identity. However, a clear divergent of position regarding religion could be seen in the respective constitutions with regard to the position of Islam and secularism. It is interesting to investigate the constitutional position of religion and the consequence of such divergent in the construction of the constitution and legislation. The paper looks at the text of the constitutions and approaches taken by the apex court in the two countries. The paper also looks at the jurisprudence of the European Court of Human Rights since Turkey is a signatory of the Convention for the Protection of Human Rights and Fundamental Freedoms. The opposing positions taken by the two constitutions with regard to the influence of religion in public affairs surprisingly offers a coherent approach in constitutional construction.